Toward Culturally and Linguistically Responsive E-Learning in Post-COVID-19 Higher Education: Perspectives from the United Arab Emirates - Sarah Hopkyns (Gulf Education and Social Policy Review)
The COVID-19 pandemic has caused dramatic shifts in education worldwide. In the spring of 2020, universities abruptly moved to emergency remote teaching and learning (ERT&L), with online and hybrid education continuing into the post-pandemic era. In the Gulf, cultural, religious, and sociolinguistic dynamics can present additional challenges for teaching and learning online. Reluctance to use cameras due to modesty, privacy, and E-safety concerns, amongst others, affects interaction and rapport. This article presents empirical data from a qualitative phenomenological case study investigating male and female Emirati university students’ (n = 107) perspectives on access, interaction, and engagement during Zoom classes in the fall of 2020 and spring of 2021. Students’ reflective essays and researcher observations revealed that intersecting factors, such as gender, religion, culture, linguistic challenges in English-medium universities, and fear of judgment, affected participants’ comfort levels and learning effectiveness in online classes. Data are analyzed through interpretive phenomenological analysis and the analytical tool of intersectionality, through which complexities of learner identities are explored. Practical suggestions are made on adapting online and hybrid learning to suit the sociocultural realities of Gulf states better by enhancing interaction and engagement in online classes without compromising comfort, E-safety, and privacy in post-pandemic education